Energy-efficient usage and investment behaviours : a case study on Singapore's hawkers - Lee, Edmond Ren Jie (2019)
Singapore’s unique hawker fare has become a quintessential component of the Singaporean identity, which underscores the need to ensure the sustainability of the hawker culture. This paper presents a timely analysis of the behaviour of hawkers in the domain of energy-efficiency, providing insights to guide future policies in improving energy-efficiency in the hawker sector, and to ensure the long-term sustainability of the hawker sector. The multivariate ordered probit models in this study found that the environmental attitudes of hawkers and knowledge on cost-savings from investing in energy-efficiency and energy-saving practices were key drivers in energy-efficiency investments. It was also found that the hawkers’ maximum acceptable payback period for investment in energy-efficient equipment has a mean of 1.91 years, compared to the actual realistic range of 3-5 years, which indicates a high implicit discount rate that leads to underinvestment into energy-efficient equipment. Policy recommendations were formulated and proposed by leveraging on established and successful existing initiatives in Singapore and abroad. The paper hopes that by emphasising on ease of implementation, energy-efficiency measures could be readily promoted amongst hawkers to combat climate change as well as preserve Singapore’s unique culture heritage.